Business Center Management (A Site Study at 1st Public Vocational School Purwokerto) - Latifah, Taty Siti (2011)
The objectives of the research are (1) to describe the characteristic of organizational structure of the business center, (2) the characteristic of the work relationship of a business center with a school, (3) the characteristic of the business center activities. This research is a qualitative research with ethnography design. The informants in this research are the principal, vice principal, business center administrators, teachers, and students. The method of collecting data used observation, in-depth interview, and documentation. Data analysis used an analysis model arranged in a site. The research results show that: (1) the organizational structure of business center program consists of the person in care taker of the program, administrators, professional staffs, and students. The person in care taker of the program is the principal who has a role and function as the person who is responsible to the business center. The administrators consist of the chairman, secretary, and treasurer who handled by the vice principal and teachers. The chairman has a responsible of the business center activities, the secretary is in charge of the administration, while the treasurer is as a staff who handle the finance. The professional staffs consist of supervisor, administrative officer, and warehouse officer. Students acts as the participants to do practice, namely the person who practice to sell the products; (2) Business center is organized as a place for training practice of students to the entrepreneurship subject. The source of fund in the business center is from the Directorate of Vocational School being managed and developed by the school as much as Rp. 250 million. The business center is managed by the school assisted by the professional staffs. In its implementation, the school selects the candidates or professional staffs and the promotion is through radio and brochure, and directly by students in practice of selling the products. Business center sell daily needs and grocery items. The selling process is done directly by the business center, and indirectly through students in selling practice with direct and order selling techniques; (3) The business center activity is started at 8 a.m. to 4.30 p.m. The business center activities are to sell in wholesale and retail. The warehouse staffs organized the circulation of the business center products, the staff serves the customers, while the administrative staffs to input data and make a financial report. The administration is accumulated in the computerized system to expedite the process and accuracy of data, being supported by the manual system which is recorded in the cash book, inventory, purchasing, sale, and so on.